Leptin and Epicardial Fat: New Markers of Psoriasis in Children? Prospective Cross-Sectional Study - Eduard T. Ambarchyan; Leila S. Namazova-Baranova; Nikolay N. Murashkin; Elena A. Vishneva; Grigoriy V. Revunenkov; Natalya G. Ovsyanik; Vladislav V. Ivanchikov; Anastasia D. Kuzminova (Union of pediatricians of Russia, 2022)
Background. Psoriasis is a polygenic multifactorial immune-mediated disease. Its course can be aggravated by associated obesity. Recently, there is negative trend that is characterized by the increase in the number of moderate to severe psoriasis cases among children, and majority of them have obesity. Identification of factors that that are relevant in these two conditions will allow us to improve and optimize the genetically engineered biological therapy for this category of patients.Objective. The aim of the study is to evaluate epicardial adipose tissue thickness, serum leptin levels, eating behavior via the data from Children's Eating Behaviour Questionnaire (CEBQ) for patients with psoriasis and obesity, and compare the results with control group - patients with psoriasis and no associated obesity.Results. We have studied 12 patients with established diagnosis of psoriasis, 5 of them had diagnosis of obesity. Epicardial fat thickening was revealed in 20% of cases in the study group (patients with psoriasis and obesity), and no epicardial fat thickening was revealed in the control group. The increase in serum leptin was revealed in 100% of cases in obese patients with psoriasis, and only in 14% of cases in the control group. The mean leptin level in obese patients was 16.65 ng/ml, in the group with normal body weight - 7.08 ng/ml. Obese patients have shown higher values in "food approach" scales group in comparison to normal weight patients.Conclusion. Patients with obesity and psoriasis has shown elevated leptin levels, higher incidence of epicardial fat thickening, and tendency to develop abnormal eating behavior.